2011
DOI: 10.1556/abiol.62.2011.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of roundup-induced toxicity on genetic material and on length growth of barley seedlings

Abstract: The study was performed in order to evaluate Roundup-induced genotoxic effects in Hordeum vulgare L. cv. Madalin root meristems and to analyze herbicide impact on length growth of barley seedlings. Caryopses were treated for 3 hours and 6 hours with 0.1%, 0.5%, 1.0% and 2.0% Roundup solutions (v/v), containing 0.36 mg ml-1, 1.8 mg ml-1, 3.6 mg ml-1 and 7.2 mg ml-1 glyphosate active ingredient. Mitotic index decreased in both exposure times with concentration increase. In 3-h treatment, its average values decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…In contrast, several studies using different tests have reported high genotoxicity for glyphosate (Sivikova and Dianovsky, 2006; Sparling et al , 2006; Cavas and Könen, 2007; Alvarez et al , 2011; Guilherme et al , 2012), with the genotoxicity observed being related to the test system used (Zñiga, 2001), e.g. , plants (Dimitrov et al , 2006; Alvarez et al , 2011; Truta et al , 2011), fish (Cavas and Könen, 2007) and human cells (De Roos et al , 2005; Bolognesi et al , 2009) are reportedly very sensitive to glyphosate.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, several studies using different tests have reported high genotoxicity for glyphosate (Sivikova and Dianovsky, 2006; Sparling et al , 2006; Cavas and Könen, 2007; Alvarez et al , 2011; Guilherme et al , 2012), with the genotoxicity observed being related to the test system used (Zñiga, 2001), e.g. , plants (Dimitrov et al , 2006; Alvarez et al , 2011; Truta et al , 2011), fish (Cavas and Könen, 2007) and human cells (De Roos et al , 2005; Bolognesi et al , 2009) are reportedly very sensitive to glyphosate.…”
Section: Introductionmentioning
confidence: 96%
“…caffeine) has been a subject of different in-vivo and in-vitro studies for many years. [26][27][28][29] These studies support genotoxic potential of caffeine to bacteria, fungi and green plants. However, genotoxic, reproductive and developmental/teratogenic risks of caffeine in humans were not confirmed, although potential risk exists at high doses of caffeine exposure to injure the human embryo.…”
Section: Introductionmentioning
confidence: 60%
“…Toxicity of naturally occurring purine alkaloids methylxanthines (e.g. caffeine) has been a subject of different in‐vivo and in‐vitro studies for many years . These studies support genotoxic potential of caffeine to bacteria, fungi and green plants.…”
Section: Introductionmentioning
confidence: 97%
“…Varios estudios que utilizan diferentes pruebas (in vivo e in vitro) han informado de alta genotoxicidad del GP (Sivikova and Dianovsky, 2006, Sparling et al, 2006, Cavas and Konen, 2007, Alvarez-Moya et al, 2011, Guilherme et al, 2012. La genotoxicidad observada está relacionada con el organismo de prueba utilizado (Zúñiga, 2001), por ejemplo, las plantas (Dimitrov et al, 2006, Alvarez-Moya et al, 2011, Truta et al, 2011, los peces (Cavas and Konen, 2007) y las células hu-manas (De Roos et al, 2005, Bolognesi et al, 2009 son muy sensibles al GP. Teniendo en cuenta la importancia de los enfoques que implican los efectos genotóxicos de los contaminantes sobre los organismos acuáticos, así como la escasez de información con respecto a estos daños genéticos producido por RT y el GP en peces, se han diseñado estudios para evaluar el daño del ADN en peces expuestos a GP y RT; uno de ellos es el ensayo cometa, ensayo conocido como SCGE (ensayo de electroforesis en gel de célula única) siendo uno de los más utilizados (Langiano and Martinez, 2008).…”
Section: Genotoxicidadunclassified